Toxicity assessment of various ionic liquid families towards Vibrio fischeri marine bacteria - Ventura, Sónia P. M. (2019)
The increasing interest on the application of ionic liquids (ILs) to a wide range of processes and products has been hampered by a lack of toxicological data, mainly in what concerns novel cations, such as guanidinium, phosphonium, and functionalized and non-functionalized imidazolium-based ILs. The present study reports the toxicity of five guanidinium-, six phosphonium, and six imidazolium-based ILs, towards the luminescent marine bacteria Vibrio fischeri. These new results clearly show that guanidinium-, unlike the imidazolium- and phosphonium-based ILs, do not follow the trend of increasing toxicity with the increase in the alkyl chain length. Moreover, the introduction of oxygenated groups on the alkyl chains, such as ether and ester, leads to a decrease of the toxicity of guanidinium and also imidazolium compounds. In what respects the effect of the different cations, it is possible to recognize that the phosphonium-based ILs seem to be more toxic when compared to the analog imidazolium-based ILs (with the same anion and alkyl chains).